(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Vitamin B12 deficiency is a common clinical problem, particularly among elderly patients, women of reproductive age, children, and adolescents. Subclinical forms often remain asymptomatic, which may delay diagnosis and lead to irreversible neurological complications. Therefore, early detection of vitamin B12 deficiency and implementation of preventive measures is of significant clinical importance.